Pathophysiology - Crutchlow, Eileen M. (Slack, 2002)
Keywords: Physiology; Pathological; Nursing; dept.nur; faculty_collection

The Pediatric Nurse's Survival Guide - Rebeschi, Lisa M. (Delmar, 2002)
Keywords: Handbooks; manuals; etc; Pediatric nursing; dept.nur; faculty_collection

Counselors’ conceptualizations of caring in the counseling relationship - Halstead, R.W.; Wagner, L.D.; Vivero, M.; Ferkol, W. (Counseling and Values, 2002)
Caring is a concept that has been studied in numerous helping professions but has yet to be researched from a counseling perspective. In this qualitative research study, 13 master’s-level counseling interns were interviewed to better understand their perceptions of caring in the counseling relationship. Results suggest that these interns perceive that supporting desired outcomes, a personal capacity for caring, maintaining therapeutic conditions, mutuality in the counseling relationship, and a dynamic flow of communication are important attributes of the counseling relationship when caring is present The findings suggest further research that explores the concept of caring in the counseling relationship may be warranted. © 2002 American Counseling Association.
2 citations (Crossref) [2023-10-31]
Keywords: dept.nur